Evaluation of the Smart Branding Strategy of Pahlawan Street Center in Strengthening the Identity of Madiun City - Indah Nastiti Wahyundari; Anindita Primastuti; Marthalina Marthalina (Sean Institute, 2026)
The development of the smart city concept has encouraged local governments to build city branding through smart branding strategies as an effort to enhance competitiveness, increase regional attractiveness, and strengthen local identity. One implementation of this strategy is manifested through the development of Pahlawan Street Center (PSC) as a flagship destination of Madiun City. Nevertheless, the existence of PSC has also generated various dynamics regarding its appropriateness in representing the distinctive identity of the region. This study aims to evaluate the strategic fit of the smart branding strategy of Pahlawan Street Center (PSC) in strengthening the identity of Madiun City, analyze the supporting and inhibiting factors, and formulate strategic recommendations. This study employed a descriptive qualitative method. Data were collected through interviews, direct observation, and documentation studies involving various informants. The strategy evaluation in this study was analyzed using John M. Bryson’s strategic management concept, which encompasses five dimensions: strategic fit, public value creation, feasibility, stakeholder support, and sustainability. The findings indicate that the smart branding strategy through PSC has been integrated with planning documents and has created tangible public value in the form of enhanced visual attractiveness of the area. However, this strategy is considered not yet optimal in strengthening the authentic local identity, as the area’s appearance is more dominated by miniature global icons that obscure the authentic local character. Supporting factors for the successful implementation of the strategy include alignment with planning documents, community economic improvement, private sector participation (CSR), digital infrastructure support, and innovative activities. Meanwhile, the inhibiting factors include city image issues, inconsistency in digital promotion, low budget realization, and infrastructure capacity constraints. This study proposes strategic recommendations to optimize the smart branding of Madiun City through the alignment of branding strategies with planning documents, the strengthening of local identity as a source of public value, the optimization of budget planning and utilization, the enhancement of collaboration among stakeholders, and the implementation of sustainable performance monitoring and program evaluation.